Comparative effectiveness of immediate antiretroviral therapy versus CD4-based initiation in HIV-positive individuals in high-income countries: observational cohort study. Issue 8 (August 2015) - Lodi, Sara; Phillips, Andrew; Logan, Roger; Olson, Ashley; Costagliola, Dominique; Abgrall, Sophie; van Sighem, Ard; Reiss, Peter; Miró, José M; Ferrer, Elena; Justice, Amy; Gandhi, Neel; et al.
Summary: Background: Recommendations have differed nationally and internationally with respect to the best time to start antiretroviral therapy (ART). We compared effectiveness of three strategies for initiation of ART in high-income countries for HIV-positive individuals who do not have AIDS: immediate initiation, initiation at a CD4 count less than 500 cells per μL, and initiation at a CD4 count less than 350 cells per μL. Methods: We used data from the HIV-CAUSAL Collaboration of cohort studies in Europe and the USA. We included 55 826 individuals aged 18 years or older who were diagnosed with HIV-1 infection between January, 2000, and September, 2013, had not started ART, did not have AIDS, and had CD4 count and HIV-RNA viral load measurements within 6 months of HIV diagnosis. We estimated relative risks of death and of death or AIDS-defining illness, mean survival time, the proportion of individuals in need of ART, and the proportion of individuals with HIV-RNA viral load less than 50 copies per mL, as would have been recorded under each ART initiation strategy after 7 years of HIV diagnosis. We used the parametric g-formula to adjust for baseline and time-varying confounders. Findings: Median CD4 count at diagnosis of HIV infection was 376 cells per μL (IQR 222–551). Compared with immediate initiation, the estimated relative risk of death was 1·02 (95% CI 1·01–1·02) when ART was started at a CD4 count less than 500 cells per μL, and 1·06 (1·04–1·08) with initiation at a CD4 count less than 350 cells per μL. Corresponding estimates for death or AIDS-defining illness were 1·06 (1·06–1·07) and 1·20 (1·17–1·23), respectively. Compared with immediate initiation, the mean survival time at 7 years with a strategy of initiation at a CD4 count less than 500 cells per μL was 2 days shorter (95% CI 1–2) and at a CD4 count less than 350 cells per μL was 5 days shorter (4–6). 7 years after diagnosis of HIV, 100%, 98·7% (95% CI 98·6–98·7), and 92·6% (92·2–92·9) of individuals would have been in need of ART with immediate initiation, initiation at a CD4 count less than 500 cells per μL, and initiation at a CD4 count less than 350 cells per μL, respectively. Corresponding proportions of individuals with HIV-RNA viral load less than 50 copies per mL at 7 years were 87·3% (87·3–88·6), 87·4% (87·4–88·6), and 83·8% (83·6–84·9). Interpretation: The benefits of immediate initiation of ART, such as prolonged survival and AIDS-free survival and increased virological suppression, were small in this high-income setting with relatively low CD4 count at HIV diagnosis. The estimated beneficial effect on AIDS is less than in recently reported randomised trials. Increasing rates of HIV testing might be as important as a policy of early initiation of ART. Funding: National Institutes of Health.